Divergent Evolutionary and Expression Patterns between Lineage Specific New Duplicate Genes and Their Parental Paralogs in Arabidopsis thaliana - Wang, Jun (Public Library of Science, 2013)

(untitled)
Gene duplication is an important mechanism for the origination of functional novelties in organisms. We performed a comparative genome analysis to systematically estimate recent lineage specific gene duplication events in Arabidopsis thaliana and further investigate whether and how these new duplicate genes (NDGs) play a functional role in the evolution and adaption of A. thaliana. We accomplished this using syntenic relationship among four closely related species, A. thaliana, A. lyrata, Capsella rubella and Brassica rapa. We identified 100 NDGs, showing clear origination patterns, whose parental genes are located in syntenic regions and/or have clear orthologs in at least one of three outgroup species. All 100 NDGs were transcribed and under functional constraints, while 24% of the NDGs have differential expression patterns compared to their parental genes. We explored the underlying evolutionary forces of these paralogous pairs through conducting neutrality tests with sequence divergence and polymorphism data. Evolution of about 15% of NDGs appeared to be driven by natural selection. Moreover, we found that 3 NDGs not only altered their expression patterns when compared with parental genes, but also evolved under positive selection. We investigated the underlying mechanisms driving the differential expression of NDGs and their parents, and found a number of NDGs had different cis-elements and methylation patterns from their parental genes. Overall, we demonstrated that NDGs acquired divergent cis-elements and methylation patterns and may experience sub-functionalization or neo-functionalization influencing the evolution and adaption of A. thaliana.